2010
DOI: 10.1302/0301-620x.92b6.23621
|View full text |Cite
|
Sign up to set email alerts
|

Radiological outcome analysis of transtrochanteric curved varus osteotomy for osteonecrosis of the femoral head at a mean follow-up of 12.4 years

Abstract: We investigated the factors related to the radiological outcome of a transtrochanteric curved varus osteotomy in patients with osteonecrosis of the hip. We reviewed 73 hips in 62 patients with a mean follow-up of 12.4 years (5 to 31.1). There were 28 men and 34 women, with a mean age of 33.3 years (15 to 68) at the time of surgery. The 73 hips were divided into two groups according to their radiological findings: group 1 showed progression of collapse and/or joint-space narrowing; group 2 had neither progressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
42
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 26 publications
2
42
0
Order By: Relevance
“…Evidence has shown that small, medially located, asymptomatic lesions may be treated with observation alone, whereas the recommended options for symptomatic precollapse stage lesions are decompression 7,86-90 , osteotomy [91][92][93][94][95][96][97][98][99][100][101][102][103][104][105][106][107][108] , and non-vascularized or vascularized bone-grafting 90,[109][110][111] . Once the early postcollapse stage is reached, total hip arthroplasty provides consistent results; however, satisfactory results have also been demonstrated with bone-grafting [112][113][114][115][116][117][118][119][120][121][122][123][124][125] .…”
Section: Table II Decision-making Hierarchymentioning
confidence: 99%
“…Evidence has shown that small, medially located, asymptomatic lesions may be treated with observation alone, whereas the recommended options for symptomatic precollapse stage lesions are decompression 7,86-90 , osteotomy [91][92][93][94][95][96][97][98][99][100][101][102][103][104][105][106][107][108] , and non-vascularized or vascularized bone-grafting 90,[109][110][111] . Once the early postcollapse stage is reached, total hip arthroplasty provides consistent results; however, satisfactory results have also been demonstrated with bone-grafting [112][113][114][115][116][117][118][119][120][121][122][123][124][125] .…”
Section: Table II Decision-making Hierarchymentioning
confidence: 99%
“…Operative management of ONFH includes joint-salvage procedures such as proximal femoral rotational osteotomy, core decompression sequestrectomy and replacement with bone grafting, non-vascularized cancellous or cortical bone grafting of the lesion, muscle-pedicle bone grafting, free vascularized fibular grafting, and multiple small tantalum pegs [3][4][5][6][7][8][9][10][11][12]. Of these, the most commonly used procedures are core decompression combined with impaction grafting of composite bone material.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, our results of TCVO were consistent with those of the previous studies on this osteotomy (Table 3). 11,14,15,17,18,19,27,28,29,30,31,32)…”
Section: Discussionmentioning
confidence: 99%
“…This osteotomy can reduce complications of conventional varus wedge osteotomy, such as elevation of the greater trochanter, nonunion of the osteotomy site, and limb length discrepancy (LLD) 9,11,12). Saito et al13) reported a 100% success rate in 4 cases of osteonecrosis of the femoral head, and the rate of satisfactory outcomes ranged from 90% to 97.3% in other studies 11,14,15)…”
mentioning
confidence: 99%